The Effect of Digitalization of Quick Reaction Team (TRC) Reporting in Improving Performance and Public Service in the Police Unit of Sumbawa Regency - Zami, Abdurrasyid Zam; Suparman, Suparman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
This study aims to test and analyze the influence of the Development of Rapid Response Team (TRC) Reporting (X1), Improvement of ASN Performance (X2), on Public Service/Public Satisfaction (Y1) at the Sumbawa Regency Civil Service Police Unit. Mixed methods were used in this study with a sequential explanatory research design that combines quantitative and qualitative approaches. Then the data analysis method through Structural Equation Modeling - Partial Least Squares (SEM-PLS). The study population consisted of 168 people, consisting of 37 internal and 131 external populations. The total sample used was 118 respondents, consisting of 26 respondents from internal ASN/TRC and 92 respondents from locations that had received TRC services, with the sampling technique using purposive sampling and accidental sampling. Primary data were collected through questionnaires that had been tested for validity and reliability, so that the instruments used were feasible and reliable. The results of the study indicate that the development of TRC reporting has a positive effect on improving ASN performance with a coefficient value of (path coefficient = 0.639; t-statistic = 8.970; p < 0.001). Development of TRC Reporting (X1) Has a Significant Effect on Public Service (Y2). A positive and significant effect was also found between the development of TRC reporting and the quality of public service, with a path coefficient of 0.731 (t-statistic = 13.282; p < 0.001). The Y2 variable, which includes public satisfaction, perceived effectiveness, accessibility, and quality of solutions, has an R-square of 0.534, indicating that 53.4% of the variation in public service can be explained by the development of TRC reporting. Thus, this study concludes that the Development of Rapid Response Team (TRC) Reporting (X1) and Improvement of ASN Performance (X2) simultaneously have a positive and significant effect on Public Service/Public Satisfaction (Y1) in the Sumbawa Regency Civil Service Police Unit.